Being old in a country with a large youth population: the case of Turkey - Kiran, Elif (Lviv Polytechnic Publishing House, 2016)
This paper focuses on the ageing issue in Turkish society and it aims to draw a general framework of the percentage and life standards of old people in the country. National statistics and social policies are the main resources used to reach this aim.
Keywords: Ageing; ageing population; Turkey; policy makers; NGOs